Therapeutic drug monitoring of psychotropic medications - Mitchell, Philip B (Blackwell Science Inc, 2001)
Therapeutic drug monitoring (TDM) of a number of psychotropic medications has proven to be of value, enabling minimization of the limitations of considerable genetic variability in their metabolism and the high rates of poor compliance with many psychiatric disorders. Therapeutic ranges have been established for lithium, some of the tricyclic antidepressants, and clozapine. TDM has also been shown to be useful in avoiding toxicity (as many psychotropics have narrow therapeutic indices), particularly that due to interactions with other compounds.